Neighbor urban wastewater treatment plants display distinct profiles of bacterial community and antibiotic resistance genes - Fernandes, Telma (2019)
Urban wastewater treatment plants (UWTPs) are among the major recipients of antibiotic-resistant bacteria (ARB), antibiotic resistance genes (ARGs), and antibiotic residues in urban environments. Although during treatment, bacteria of human and animal origin are removed, some are able to survive, persisting in the final effluent. The occurrence of these bacteria, especially those harboring ARGs, may have a direct impact on the quality of the treated wastewater that is returned to the environment. In this study, we aimed to assess if the final effluent bacterial communities of three UWTPs (PT1, PT2, and PT3) located next to each other were distinct and if such differences were related with the antibiotic resistance profiles. It was observed that the bacterial community (16S rRNA gene Illumina sequencing) and load of selected ARGs of final effluent differed among the three UWTPs, irrespective of sampling time. Members of the families Aeromonadaceae, Campylobacteraceae, Veillonellaceae, [Weeksellaceae], and Porphyromonadaceae were observed to be positively correlated with some ARGs (bla(CTX-M), bla(OXA-A), bla(SHV)) and intI1 (p < 0.05), while Intrasporangiaceae were observed to be negatively correlated. While Aeromonadaceae are recognized relevant ARG harbors, the other bacterial families may represent bacteria that co-exist with the ARG hosts, which may belong to minor bacterial groups omitted in the analyses. These findings suggest the importance of bacterial dynamics during treatment to the ARB&ARGs removal, a rationale that may contribute to design new strategies to apply in the UWTPs to prevent the spread of antibiotic resistance.